Segmenting urban populations for greater conservation gains: A new approach targeting cobenefits is required. Issue 10 (7th August 2019) - MacDonald, Edith; Harbrow, Michael; Jack, Sandra; Kidd, Julie; Wright, Andrew; Tuinder, Pieter; Balanovic, Jovana; Medvecky, Fabien; Poutasi, Markerita
Abstract: Engaging urban residents in greater proconservation behaviors is essential to mitigate the biodiversity crisis. To date, most behavior‐change campaigns have been based on a one‐size‐fits‐all "think‐care‐act" approach resulting in insufficient, sometimes counterproductive, conservation gains. In our study, we assess the "think‐care‐act" paradigm and also consider a range of cobenefits that may motivate different segments of urban populations to take greater conservation action for reasons other than biodiversity gains. We surveyed a representative sample of Auckland, New Zealand ( n = 2, 124) and four clusters emerged through clustering analysis. The first segment ( Environmentally Active ; 32%), exhibited the "think‐care‐act" paradigm. The second segment ( Well Informed ; 28%), was highly knowledgeable and concerned about conservation problems but exhibited lower conservation behaviors. The third segment ( Active Outdoors ; 19%) was actively engaged in outdoor activities, but exhibited low conservation knowledge, concern, and behaviors. The fourth segment ( Socially Motivated ; 21%), demonstrated high levels of conservation behaviors but lower knowledge and concern about conservation issues. We discuss potential ways to engage with each segment based on cobenefits and the need to move away from the traditional "think‐care‐act" paradigm and instead work with existing values systems and foster greater conservation behavior based on existing cobenefits.